Deli Maatschappij: A Look at the Initial Company as a Result of the Dutch East Indies Open Door Policy - Muhammad, Ulul Azmi; Kurniawan, Amar Ageng (Riwayat: Educational Journal of History and Humanities, 2025)
The Dutch colonial period in the archipelago witnessed various significant changes in aspects of government and economic policies, one of which was the implementation of the Forced Planting System in the early 19th century, which led to suffering for local farmers. In 1870, the Dutch government replaced this system with open-door politics, which opened up opportunities for private companies, including the Deli Company (Deli Maatschappij) founded in 1869. Deli Maatschappij, which began with tobacco plantations in East Sumatra, grew rapidly and became the dominant force in the international tobacco industry until the early 20th century. This article aims to examine the history of the establishment and development of Deli Maatschappij, as well as its impact on the lives of workers and the local community. This research uses historical research methods with heuristic, critical, interpretation, and historiographic stages. The results show that Deli Maatschappij not only drives economic development through infrastructure and industry, but also contributes to social and demographic change, including the influence on the labor system and social relations in the region. Despite negative impacts such as labor exploitation, the company has also made some progress, such as the development of transportation and education infrastructure that has survived to this day.